Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction